Insider Threats in Cyber Security - Probst, Christian W.; Hunker, Jeffrey; Bishop, Matt.; Gollmann, Dieter; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Insider Threats in Cyber Security is a cutting edge text presenting IT and non-IT facets of insider threats together. This volume brings together a critical mass of well-established worldwide researchers, and provides a unique multidisciplinary overview. Monica van Huystee, Senior Policy Advisor at MCI, Ontario, Canada comments "The book will be a must read, so of course I’ll need a copy." Insider Threats in Cyber Security covers all aspects of insider threats, from motivation to mitigation. It includes how to monitor insider threats (and what to monitor for), how to mitigate insider threats, and related topics and case studies. Insider Threats in Cyber Security is intended for a professional audience composed of the military, government policy makers and banking; financing companies focusing on the Secure Cyberspace industry. This book is also suitable for advanced-level students and researchers in computer science as a secondary text or reference book.
Aspects of Insider Threats -- Combatting Insider Threats -- Insider Threat and Information Security Management -- A State of the Art Survey of Fraud Detection Technology -- Combining Traditional Cyber Security Audit Data with Psychosocial Data: Towards Predictive Modeling for Insider Threat Mitigation -- A Risk Management Approach to the “Insider Threat” -- Legally Sustainable Solutions for Privacy Issues in Collaborative Fraud Detection -- Towards an Access-Control Framework for Countering Insider Threats -- Monitoring Technologies for Mitigating Insider Threats -- Insider Threat Specification as a Threat Mitigation Technique.
Keywords: Computer security; Computer communication systems; Data encryption (Computer science).; Application software; Data structures (Computer science).; Computer organization; Systems and Data Security; Computer Communication Networks; Cryptology; Information Systems Applications (incl. Internet).; Data Structures and Information Theory; Computer Systems Organization and Communication Networks